Hatred of America's presidents : personal attacks on the White House from Washington to Trump - Han, Lori Cox (ABC-CLIO, 2018)
This work examines expressions of personal hostility and animosity toward presidents--even beloved ones--throughout American history and their impact on policymaking, politics, and culture. The book details representative and commonplace vitriolic, personal attacks, who instigated the attacks and how presidents, administrations, and political parties defended themselves. It shows how honest disagreements about policy fueled condemnation and includes both parties' perspectives.